FUNGSI KESENIAN KUDA LUMPING BAGI MASYARAKAT DESA RAMBAH BARU KECAMATAN RAMBAH SAMO KABUPATEN ROKAN HULU - Budi, Agus Setiyo; Bahri, Syamsul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Kuda lumping is a javanesse traditional art which brings the heroism or heroic message. The purpose of the research are knowing the process of kuda lumping performance in the village rambah baru and function art of kuda lumping for the people in village rambah baru. The method used in this research is descriptive Qualitative Research method, namely the disussion of this research is presented and analyzed in the form of a description of the words (description) with a qualitative approach. This research also supported by the implementation of indepth interviews with the informants (informants) that have been determined in advance by researchers. Based on the result in the art of kuda lumping in village rambah baru is performance started by doing rituals such as burning the incense and using sesajen. Adter that, the dance of kuda lumping the gamelan accompaniment began to appear until it entered the trance stage. While the function of Kuda lumping art for new communities includes functions as entertainment, educational facilities, to commemorate festivities and also function in the economic field. Because Indonesia has a variety of ethnicities, the story of the origin of the lumping horse art varies according to each region. In the performance, kuda lumping uses bamboo webbing that shaped of horse and horsewhip.Â Â Keywords: Performance, Function, Art of Kuda Lumping